(untitled) (Journal of Nepal Geological Society, 2016)
The Dharan–Mulghat area of the eastern Nepal can be divided into three tectonic units: the Higher Himalayan Crystallines, the Lesser Himalayan Sequence and the Siwaliks from north to south separated by the Main Central Thrust (MCT) and Main Boundary Thrust (MBT), respectively. The Lesser Himalayan Sequence is divided into two groups separated by Chimra Thrust: the Bhedetar Group and the Dada Bajar Group. The Bhedetar Group includes the Raguwa Formation, the Phalametar Quartzite, the Churibas Formation, the Sangure Quartzite, and the Karkichhap Formation from the bottom to top, respectively; overthrusted by the Dada Bajar Group consisting: the Ukhudanda Formation, the Mulghat Formation, the Okhre Formation, and the Patigau Formation, from lower to upper sections, respectively along the Chimra Thrust and the Bhorleni Formation as an individual formation overthrusted by Bhedetar Group along the Chhotimorang Thrust. The Main Central Thrust, the Main Boundary Thrust, the Chimra Thrust and the Chhotimorang Thrust are the major faults in Dharan–Mulghat area. The Leutiphedi Anticline and the Malbase Syncline are the major folds in the study area plunging towards east. The trend/plunge of anticline and syncline are 131o/24o and 096o/09o respectively. The microstructural study in the quartz grains reveals a sharp difference in the history across the MCT; dynamic in the rocks of the Lesser Himalayan Sequences and static in the rocks of the Higher Himalayan Crystallines.